Strategi Pengendalian Pencemaran Perairan Danau Sentani di Distrik Sentani Timur, Kabupaten Jayapura - Morin, Ciana Magdalena; Muhammad, Fuad; Maryono (Jurnal Teknologi Lingkungan, 2024)
Sentani Lake, one of Indonesia's national priority lakes, serves a multitude of roles, including ecological, economic, tourism, and transportation functions. The local community has been exploring Sentani's Lake natural resources and potentials, which could potentially pose the lake to pollution and environmental deterioration. Pollution and environmental degradation are mainly caused by the erosion of the lake's boundaries and catchment areas, human settlements, transportation activities, agriculture, mining, and the use of floating net cage aquaculture. This research was performed to propose an effective pollution control strategy for Sentani Lake, with a particular focus on the East Sentani District. This descriptive quantitative research involved respondents who were selected using a purposive random sampling technique. In this research, SWOT analysis was employed to identify and formulate priority strategies for pollution control. The findings of this study underscore the paramount importance of water quality improvement strategies through concerted pollution control and environmental preservation efforts to be carried out by the Jayapura Regency Government. Those strategies require solid collaboration with traditional leaders and robust engagement with the local community. The key components of the strategies include augmenting the frequency of water quality monitoring, strategic planning and construction of domestic wastewater treatment facilities, fostering knowledge and expertise in floating net cage aquaculture, and enlisting the guidance of traditional leaders in delineating zones for the responsible utilization of Sentani Lake waters. ABSTRAK Sebagai salah satu danau prioritas nasional di Indonesia, Danau Sentani memiliki banyak fungsi seperti fungsi ekologi, ekonomi, pariwisata, dan transportasi. Masyarakat sudah sejak lama memanfaatkan potensi yang dimiliki Danau Sentani, tetapi pemanfaatan ekosistem danau dapat menimbulkan permasalahan berupa pencemaran dan kerusakan lingkungan danau. Pencemaran dan kerusakan tersebut disebabkan oleh rusaknya sempadan dan daerah tangkapan air, pemukiman penduduk, transportasi, pertanian, pertambangan, dan kegiatan perikanan budidaya keramba jaring apung (KJA). Tujuan dari penelitian deskriptif kuantitatif ini adalah untuk merumuskan strategi pengendalian pencemaran perairan danau khususnya di wilayah Distrik Sentani Timur. Penelitian ini menggunakan metode purposive random sampling untuk menentukan responden dan analisis SWOT untuk mengidentifikasi serta merumuskan prioritas strategi pengendalian pencemaran. Hasil penelitian menunjukkan bahwa strategi prioritas yang tepat untuk pengendalian pencemaran adalah meningkatkan kualitas perairan Danau Sentani melalui pengendalian pencemaran dan kerusakan lingkungan oleh Pemerintah Kabupaten Jayapura dengan dukungan tokoh adat dan masyarakat,  menambah frekuensi pemantauan kualitas air, perencanaan dan pembangunan IPAL domestik, meningkatkan pengetahuan dan ketrampilan budidaya KJA serta melibatkan tokoh adat untuk menetapkan zonasi pemanfaatan perairan danau.